A Comprehensive Review on Gesture-Controlled Smart Home Systems for Elderly and Disabled Individuals - KB, Pradeep Rao; Biradar, Sharanabasava; Devadiga, Shreyas; Dalabanjan, Vishal T; MM, Vijay (International Journal of Computer Sciences and Engineering, 2025)
The increasing global population of elderly and physically disabled individuals has highlighted the urgent need for accessible and inclusive smart home technologies. Gesture-controlled systems offer a promising, non-verbal interface for home automation, enabling greater independence and reducing reliance on caregivers. This survey presents a comprehensive review of gesture-based smart home systems specifically designed for elderly and physically impaired users, focusing on technological advancements, usability, and system-level challenges. The study systematically examines literature from the past decade, analyzing key dimensions including gesture recognition methods, sensor modalities, system integration, user accessibility and security. Deep learning techniques such as convolutional neural networks (CNNs) and sensor fusion approaches have led to improved gesture recognition accuracy. However, issues such as environmental sensitivity, limited real-world validation, and lack of standardized benchmarks persist. A chronological review traces the evolution of these systems—from early infrared and wearable technologies to current AI-enhanced, IoT-integrated, multimodal platforms. Despite technical progress, challenges remain in terms of user fatigue, gesture variability, hardware intrusiveness, and inconsistent evaluation methodologies. Moreover, critical aspects such as security, scalability, and personalized interaction are often underexplored. This review identifies major research gaps and proposes future directions including the development of adaptive gesture sets, robust multimodal frameworks, ergonomic sensor designs, and privacy-aware authentication mechanisms. Emphasis is placed on user- centered design and longitudinal field testing to enhance practical applicability. By consolidating current knowledge and highlighting future opportunities, this review aims to guide researchers and developers toward creating inclusive, reliable, and scalable gesture-controlled smart home systems that better support the needs of elderly and disabled individuals